IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE BY USING ENVIRONMENTAL MEDIA - Yunita Mutiara Harahap; Ningrum Wijati Harahap; Linda Anisa (Pedagogi: Jurnal Ilmiah Pendidikan, 2021)
This study attempted to improve students’ descriptive text writing through environtmental media. It was conducted by using classroom action research. The subject of the research was the eighth grade students of SMP Al Washliyah 4 Medan consisting of 18 students. The research was conducted in two cycles and each cycle consisted of three meetings. The instruments for collecting data were essay test, observation sheet, diary notes, and questionnaire sheet. Based on the descriptive text test results, students’ score kept improving in every test. In the orientation test, there were 8 students getting ≥75 and the mean was 66. In the first cycle, there were 9 students obtaining ≥75, and the mean was 71. In the second cycle, there were 15 students gaining ≥75 and the mean was 83. Based on the diary notes and questionnaire sheet, it was shown that the expression and excitement of the students in studying descriptive text writing also improved. Based on the diary notes and observation, it was found that the teaching learning process ran well, the students were active and interested in studying descriptive text writing. Thus, the results of research showed that the environtmental media improved students’ descriptive text writing.